1984
DOI: 10.1007/bf00033388
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the translation start site of the large subunit of ribulose-1,5-bisphosphate carboxylase from maize

Abstract: Sequence studies of the gene for the large subunit of ribulose-1,5-bisphosphate carboxylase from maize indicate the presence of two translation start sites, 18 bp apart. Each site is preceded by a suitable ribosome binding region. By using a simplified E. coli-based in vitro system which measures fromation of the first dipeptide of the gene product, we have determined that only the second methionine initiates translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Both of these sequence regions also contain potential ribosomal binding sites that are homologous to the 16S rRNA from maize (38). Experiments in this laboratory, using different tRNA isoacceptor species, have shown that the first dipeptide of the protein is synthesized from the second fMet-Ser sequence of the maize rbcL gene and that the other possible start site 18 bp upstream is not recognized (39).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these sequence regions also contain potential ribosomal binding sites that are homologous to the 16S rRNA from maize (38). Experiments in this laboratory, using different tRNA isoacceptor species, have shown that the first dipeptide of the protein is synthesized from the second fMet-Ser sequence of the maize rbcL gene and that the other possible start site 18 bp upstream is not recognized (39).…”
Section: Discussionmentioning
confidence: 99%
“…changes, (13/477; 99.97% homology) 46X are non-conservative. The second ATG (+1) in the open reading frame is the probable translation start site (2,3). ATC TCA CCA CAA ACA CAC ACT AAA CCA ACT CTT CCA TTC AAA CCT ACT GTT AAA CAC TAC AAC TTC ACT TAT TAT ACT CCT CAC TAC CAA CCC AAC CAT ACT CAT ATA TTC CCA CCA TTC H S P Q T E T K A S…”
mentioning
confidence: 99%